Conservation of Astrocaryum aculeatum seeds as a function of storage conditions of diaspores - Rebouças, Elizabeth Rodrigues; Ferreira, Sidney Alberto do Nascimento; Nazário, Patrícia; Gentil, Daniel Felipe de Oliveira (Comunicata Scientiae, 2025)
Information on the conservation of Astrocaryum aculeatum seeds can contribute to the sustainable management of this species, as commercial harvesting of its fruits is essentially extractivist. Thus, the objective of this study was to evaluate the germination and vigor of A. aculeatum seeds based on the storage conditions of diaspores (seeds with endocarp). A completely randomized experimental design was used, with a split-plot arrangement in time and four replications. Diaspores containing seeds with 21.1% moisture content were packaged and stored under the following conditions: a) permeable packaging in a natural environment (air temperature of 27.7 ± 1.5 °C and relative air humidity of 85.0 ± 11.9%); b) impermeable packaging in a natural environment; c) impermeable packaging in a cold chamber (18.0 ± 1.0 ºC and relative air humidity of 68.1 ± 6.2%). Seed moisture content, germination, dormancy, and mortality, percentage of seedling emergence, emergence speed index, and mean emergence time were evaluated after different storage periods (0, 2, 4, 6, and 10 months). Storing diaspores of A. aculeatum in impermeable packaging in a natural environment effectively preserve seed physiological quality for ten months. Contrastingly, storing diaspores in permeable packaging in a natural environment and in impermeable packaging in a cold chamber reduces seed physiological quality after two to three months of storage.